Care management in the work process of hospital Nurse: An integrative review (Research, Society and Development, 2023)
Introduction: This study aims to identify, gather and synthesize the evidence available in the national and international literature on the application of care management in the hospital context. Methodology: Integrative review, using the databases, Medline, Lilacs and Scielo, in the languages Portuguese, English and Spanish, with articles published between 2017 and 2022. Results: Out of the 224 articles selected, 13 articles were analyzed, three from Medline, two from Lilacs and eight from Scielo. Discussion: Two categories were established, among them, leadership as a primary managerial competence in their work process; and Facilities/limitations in the professional praxis of hospital nurses. Final considerations: Through the evidence in the literature, the importance of managing the care offered by hospital nurses was perceived, providing autonomy for the performance of a humanized and integral service to the patient.